Nutritional value and yield of oat grain - Đekić Vera; Staletić Mirjana; Milivojević Jelena; Popović Vera; Jelić Miodrag (Agroznanje, 2012)
The investigation was carried out on the experimental field of Small Grains Research Centre, Kragujevac, and the aim of exploration was to determine the nutritional value and yield of oat grain in terms of its use in livestock feed. This paper presents the results of Kragujevac varieties of spring oats (Slavuj, Vranac and Lovcen). Grain yield, 1,000 kernel weight and protein content in the grains of three oat cultivars were determined in a two-year field experiment. The average grain yield of oat cultivars ranged from 3.281 t/ha to 4.792 t/ha. Slightly higher average values of grain yield were found in 2007. Average values of 1,000 grain weight of oat cultivars varied in the range from 26.90 to 30.80 g. The results show that there are significant differences between cultivars, whilst the average protein content ranged from 11.05% to 12.88%. The year 2006 was significantly more favourable than 2007 for protein synthesis. It seems that this is due to a cultivar property, but it is also under a very strong environmental influence. The examined material could therefore be valuable both in terms of growing oats as a forage crop plant and in terms of breeding processes regarding grain quality and productivity.